Systematic review of screening tools for common soccer injuries and their risk factors - Raphael Christopher; Corlia Brandt; Natalie Benjamin-Damon (AOSIS, 2021)
Background: Several screening tools are available for use in a clinical setting to predict injury. However, there is a lack of evidence regarding the accuracy of these tools to predict soccer-specific injuries. Objectives: The purpose of this systematic literature review was to determine the psychometric properties or accuracy of screening tools for common soccer injuries. Methods: A systematic review of diagnostic test accuracy was undertaken based on the Joanna Briggs Institute (JBI) procedure for conducting systematic reviews. Databases such as SPORT Discus, Cinahl, Medline, Science Direct, PubMed and grey literature were searched in order to access suitable studies. Results: A total of 10 studies were included for the analysis - three were analysed quantitatively whilst the remaining seven were analysed qualitatively. The screening tools were of high reliability, sensitivity and specificity (calculated as intraclass correlation coefficient [ICC] (0.68 95% confidence interval [CI]: 0.52-0.84 and 0.64 95% CI: 0.61-0.66, respectively). Conclusion: The screening tools assessed for the prediction of common soccer injuries that emerged from this systematic review include the Functional Movement Screening (FMS™), the Landing Error Scoring System (LESS), the Tuck Jump Assessment, the Soccer Injury Movement Screening (SIMS) and the conventional hamstrings to quadriceps ratio; all with good evidence of predicting common soccer injuries. These tools were of high sensitivity and specificity thus reliable for soccer screening. Clinical implications: The validity of these tools is acceptable and therefore the authors recommend that these tools be included in an injury prevention programme for soccer players.